multicultural citizenship education and the community of philosophical inquiry - park, sang wook (childhood & philosophy, 2024)
Modern civic education in multicultural society faces two diametrically opposed challenges: universality and diversity. Those who emphasize universality argue that multicultural civic education should be based on universal values, goals, and concepts. However, those who emphasize diversity say that different concepts and ideals should be allowed and respected across cultures, genders, ethnicities, etc. Multicultural education aims to promote the coexistence of people from different cultural backgrounds within a nation. In this article, I seek a way between these two extremes by arguing that civic education in a multicultural society should have philosophical inquiry and dialogue as its pedagogical basis. Providing a path to objective meaning while honoring different cultural contexts and situations. Educational efforts to achieve objectivity while respecting diversity can offer important contributions to building democratic societies that allow people who share diverse interests to interact freely. I justify this middle way by drawing upon Robert B. Brandom’s (1994, 2001) inferentialism, in which the objectivity of meaning is secured through a process of material inference that takes into account different cultural and social contexts. I conclude that the kind of dialogue Brandom has in mind is best realized through the community of philosophical inquiry, with its emphasis on reasonableness and self-correction. Ultimately, the community of philosophical inquiry is the pedagogy needed by multicultural citizenship education.